City, Farm and sea - Pike, Katy (Glebe NSW: Blake Publishing, 2013)
In the book City, Farm and Sea, the teaching focus is an information report (Animals Around Us). Students learn that different animals live in different environments. Some animals live by the sea. Others live on farms. What animals live near your home?
coloured illustrations